The Effects of Soy Bean Flour Enriched Bread Intake on Anthropometric Indices and Blood Pressure in Type 2 Diabetic Women: A Crossover Randomized Controlled Clinical Trial - Asma Salari Moghaddam; Mohammad Hassan Entezari; Bijan Iraj; Gholamreza Askari; Elham Sharifi Zahabi; Mohammad Reza Maracy (International Journal of Endocrinology)
Previous studies showed that soy bean has the potential to improve many aspects of diabetes state and provide metabolic benefits that aid in weight management. We aimed to determine the effects of soy bean flour enriched bread on anthropometric indices and blood pressure among type 2 diabetic patients. This randomized, crossover, clinical trial was performed in 30 type 2 diabetic women. There were two trial periods for 6 weeks and a wash-out period for 4 weeks. In the soy bread diet period, 120 g of soy bean flour enriched bread was consumed each day instead of the same amount of their usual bread or other cereal products. After a 4-week wash-out period, participants were crossed over for another 6 weeks. Mean (±SD) age of study participants was 45.7 ± 3.8 years. The results of our study showed no significant effects of soy bean flour enriched bread on anthropometric indices and blood pressure among diabetic patients. Despite the slight reduction in BMI, waist circumference, and percent of body fat, there were no significant differences in changes of these values between two groups. No significant changes in waist to hip ratio and blood pressure were seen.